The Peculiarities of Value-Motivation Structure of Men and Women in the Sphere of Labour and Employment - ГладниковаЕкатерина Владимировна (Journal of Economic Sociology, 2010)
In the nearest past Russia suffered great changes that touched the society life including employment sphere. The author focuses on one of the employment problem – value-motivation structure, especially gender differences in motivation and value changes that occurred since 1990s. The author states that two opposite processes could be seen in this sphere. On the one hand we trace the bias of labour motivation and employment values. On the other hand we see the reproduction of traditional labour values driven by the inertia. The paper tries to disclose these main lines of changes in labour field and to fix the keep of traditional attitudes as well.